Analysis of spontaneous reporting of suspected adverse drug reactions for non-analgesic over-the-counter drugs from 2008 to 2017 - Josipa Bukic; Doris Rusic; Petar Mas; Deni Karabatic; Josko Bozic; Ana Seselja Perisin; Dario Leskur; Darko Krnic; Sinisa Tomic; Darko Modun (BMC Pharmacology and Toxicology, 2019)
Abstract Background Adverse drug reaction (ADR) reporting practices by health care professionals remain poor. Over-the-counter (OTC) drugs are perceived as safe; however, they can also cause ADRs. The objective of this study was to analyze ADR reporting for OTC drugs in a 10-year period, in order to evaluate frequency of ADRs, population that ADRs most affect and reporters of ADRs of OTC drugs in Croatia. Methods Spontaneously reported ADRs of non-analgesic OTC drugs, collected from January 2008 to December 2017 were analyzed. Data was obtained from Agency for Medicinal Products and Medical Devices of Croatia (HALMED). Results There were 547 ADRs of OTC drugs reported in total and an increase in number of reports through the years was observed. Pharmacists reported 45.4% of all ADRs, and were most frequent reporters (p < 0.001). In 2017 majority of reports, 62 (49.2%), were obtained from consumers. ADRs were most frequently observed in patients aged 70 years and older (15% of ADRs). Five percent of all reports were accidental exposures among children. Conclusions Pharmacists most frequently reported ADRs of OTC drugs and consumers’ awareness of ADR reporting has risen. Other health care professionals (e.g., nurses and dentists) must be offered proper education in order to improve reporting practice of ADRs. Health care professionals should address concerns about OTC drug safety in elderly and children.